RiceMoRe – The digital solution for monitoring and reporting rice activities at different management levels - Bui, Tan Yen; Nguyen, Bao Tran; Nelson, Katherine M.; Vu, Hong Trang; Sander, Bjoern Ole (International Rice Research Institute, 2024)
This publication presents the success story of a digital MRV solution designed to enhance rice management and facilitate MRV of low-emission practices in rice cultivation. This initiative was co-created and implemented in Vietnam from 2018 to 2024. Additionally, we highlight RiceMoRe’s readiness for replication in other countries across the SEA region and beyond.